2022
DOI: 10.1111/1753-0407.13262
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide changes in abdominal subcutaneous and visceral adipose tissue among diabetic and nondiabetic patients

Abstract: Background This study profiles ceramides extracted from visceral and subcutaneous adipose tissue of human subjects by liquid chromatography‐mass spectrometry to determine a correlation with status of diabetes and gender. Methods Samples of visceral and abdominal wall subcutaneous adipose tissue (n = 36 and n = 31, respectively) were taken during laparoscopic surgery from 36 patients (14 nondiabetic, 22 diabetic and prediabetic) undergoing bariatric surgery with a body mass index (BMI) >35 kg/m2 with ≥1 existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…With the advent of LC-MS, the rapid and precise identification and quantification of endogenous lipids can be achieved. Brusatori M [51]analyzed the content of ceramide in human visceral and subcutaneous adipose tissue by LC-MS and found that ceramide was correlated with diabetes and gender. Cho HE [18] achieved the distinction and quantification of C18-L-threo-sphinganine and the diastereomer C18-D-erythro-sphinganine in human plasma by HILIC-LC-MS. Brogden [52] conducted qualitative and quantitative studies on sphingosine and sphinganine by chemical derivatization and liquid phase-fluorescence detection.…”
Section: Combination Of the Background Deduction Methods And Matrix S...mentioning
confidence: 99%
“…With the advent of LC-MS, the rapid and precise identification and quantification of endogenous lipids can be achieved. Brusatori M [51]analyzed the content of ceramide in human visceral and subcutaneous adipose tissue by LC-MS and found that ceramide was correlated with diabetes and gender. Cho HE [18] achieved the distinction and quantification of C18-L-threo-sphinganine and the diastereomer C18-D-erythro-sphinganine in human plasma by HILIC-LC-MS. Brogden [52] conducted qualitative and quantitative studies on sphingosine and sphinganine by chemical derivatization and liquid phase-fluorescence detection.…”
Section: Combination Of the Background Deduction Methods And Matrix S...mentioning
confidence: 99%
“…В висцеральной ткани у пациентов с диабетом и предиабетом повышено содержание Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/18:1), Cer(d18:1/20:0), Cer(d18:1/24:1) в отличие от недиабетических субъектов [60]. Аналогичный результат получили B. Choromańska и соавт.…”
Section: сравнение подкожного и висцерального жираunclassified
“…Ceramide levels have been associated with glucose metabolism dysregulation 23,24 and subsequent IR in humans, albeit the precise mechanism is unknown. Reducing peripheral glucose absorption, inactivating Akt and generating an inflammatory milieu (activating tumour necrosis factor‐alpha) are all conceivable mechanisms that have been proposed for how a high concentration of ceramides could cause IR 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…Reducing peripheral glucose absorption, inactivating Akt and generating an inflammatory milieu (activating tumour necrosis factor-alpha) are all conceivable mechanisms that have been proposed for how a high concentration of ceramides could cause IR. [25][26][27] In sub-Saharan Africa, there is very little information or data on the role of circulating ceramides and IR. Currently, available treatment options for IR and T2DM focus on lowering cholesterol and triglycerides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation